Traveling Abroad of Thai Working People in Bangkok, Thailand - Katanyu Hiransomboon (My University, 2018)
This study aims to search for traveling behavior and the marketing mix levels affecting traveling abroad of Thai working people in Bangkok.The data were collected from 400 working people by using questionnaires.The statistical method used included frequency, percentage, mean, standard deviation-test was used to evaluate the mean between two groups, F-test for one-way analysis of variance (One-way ANOVA) The results were that, most Thai tourist were women, 26-35 years old, single, company employees, bachelor degree, and more than 35,000-baht monthly income.They traveled abroad to enjoy and relax, preferred natural tourist attraction in Asian country out of ASEAN, used vacation period, spent 5-7 days, traveled once a year, budgeted 20,001-40,000 baht excluded shopping expenses, paid cash, managed their own program and reservation, and traveled with family.The levels of marketing mix implemented ranking respectively were 1) personnel 2) service process 3) tourism product 4) contact/reservation channel 5) physical evidence 6) traveling expense and 7) marketing promotion.Thai working women emphasized on traveling expense and marketing promotion more than men.Working people who went to Oceania country, Europe & America and ASEAN country had different tourism product.Thai tourist who spent 2-4 days and 5-7 days had different tourism product and physical evidence.And different travel companion affected on service personnel and physical evidence.
Keywords: Socioeconomic Development in Asia